White-light emission from a single organic compound with unique self-folded conformation and multistimuli responsiveness. Issue 26 (31st May 2018) - Li, Dengfeng; Hu, Wende; Wang, Jie; Zhang, Qiwei; Cao, Xiao-Ming; Ma, Xiang; Tian, He
Abstract : White-light emission from a single molecule was realized and tuned via multistimuli including excitation, solvent polarity, temperature and host–guest interactions. Abstract : White-light emitting organic materials attract broad attention which are ascribed to their potential for applications in lighting devices and display media. Most reported organic white-light emitters rely on the combination of several components that emit different colors of light (red/green/blue or orange/blue), which may cause problems to stability, reproducibility and device fabrication. By contrast, white-light emission from single-molecule systems offers opportunities to overcome these disadvantages, meanwhile engendering white-light with high quality. Nevertheless, limited cases of white-light emission at the molecular scale reported principally concentrate on organic solvents. Herein, we designed and synthesized new bi-functional organic molecules with a symmetric donor–acceptor–donor (D–A–D) type structure with the aim to construct a single-molecule white-light emitting system in aqueous solution. Further experiments and calculations demonstrate the possibility of stacking between the pyridinium-naphthalene (PN) core and coumarin groups in the designed molecules, ascribed to hydrophobic effects, π–π stacking and donor–acceptor interactions, which could dramatically enhance the intramolecular charge transfer (ICT) efficiency along with remarkable charge transfer (CT) emission. Based on this, multicolor photoluminescence including white-light can be finely tuned in various modes including excitation wavelength, solvent polarity, temperature, and host–guest interactions. A white-light emitting (WLE) hydrogel was also facilely prepared through the dispersion of one of the compounds in a commercial agarose gelator. This innovative study helps enrich the strategies to construct single-molecule organic white-light emitting materials in aqueous medium using the self-folding behavior.